Ant diversity under three coverages in a Neotropical coffee landscape - García-Cárdenas, Rocío (2018)
The coffee cultivation has displaced natural vegetation and its associated biological diversity. The present study describes the diversity of ground-dwelling ants on eight plantations where coffee is grown in the shade (SHD), eight plantations where coffee is grown under unshaded coffee (SUN) and four patches of forest (FOS) in a coffee-growing region of Colombia. The research was conducted in transects composed of 12 sampling stations, each of which employed active collection, pitfall traps and litter sifting. Nine habitat variables were analyzed to characterize each site, and these values were related to the diversity of ants and functional groups. A total of 92 morphospecies were collected. Myrmicinae was the subfamily with the highest representation. The sample coverage presented a deficit of less than 5 %. The rank abundance curves exhibited differences in the ant assemblages. The ant communities found in the forest exhibited greater diversity and a larger number of exclusive species than the communities found in locations of other land uses; the SHD and SUN communities were characterized by 80.3 % and 62.3 %, respectively, of the diversity found in the forest communities. The functional similarity index as adapted for guilds by Sørensen reveals a high degree of similarity in the structure of their ant communities, but less so in their composition. The shaded coffee plantations have a richer and more equitable ant fauna than the exposed coffee plantations, reinforcing the idea that shade cultivation favors the establishment of ant fauna and, consequently, ecological functionality. The shaded coffee plantations have a richer and more equitable ant fauna than the exposed coffee plantations, reinforcing the idea that shade cultivation favors the establishment of ant fauna and, consequently, ecological functionality.